Birth Length, Diarrheal and Acute Respiratory Infection Risk of Stunting in Toddlers - Musni, Musni; Malka, St.; Fatimah, Sitti; Mutmainnah, Mutmainnah (Newinera Publisher, 2024)
Stunting is a linear growth disorder that is indicated by length / age Z score less than minus 2 SD, and categorized as low nutritional status. Short birth length, Infectious diseases such as diarrhea, and Acute Respiratory Infection are indicated to be factors that cause stunting. Objectives The study aimed to analyze the risk factors of short birth length, diarrheal disease, and acute respiratory infection of stunting among children 12-59 months. Methods The study used is quantitative witch a designed case-control study. The subjects were children between 12-59 months. The sample in this study was 120 consisting of 40 stunted and 80 normal. Subjects were chosen by purposive sampling methods. instrument of this research is microtonal, weight scale, and questionnaire. The results of the study were analyzed by chi-square statistics, odds ratio, and logistic regression. The results showed that birth length (PBL) (P = 0.001), diarrhea (P = 0.000), and ARI (P = 0.030) were associated with stunting in children under five. However, after multiple logistic regression analyses, ARI was not significantly associated (P = 0.126). The risk factors for stunting in children under five are diarrhea (OR = 58.134) and short birth length (OR = 9.625).Conclusion: The risk factors for stunting were short birth length and diarrheal disease.